2010
DOI: 10.1038/onc.2010.286
|View full text |Cite
|
Sign up to set email alerts
|

Targeting anthracyclines in early breast cancer: new candidate predictive biomarkers emerge

Abstract: The search for a predictive marker of sensitivity to anthracycline-based chemotherapy has proven challenging. Despite human epidermal growth factor receptor 2 (HER2) being a strong prognostic marker in breast cancer, the only therapies with which there is a recognized functional link to the HER2 oncogene are those directly targeting the molecule itself. Despite this, HER2 has been extensively assessed as a predictive marker in a variety of chemotherapy regimens including anthracyclines. Analysis of anthracycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 90 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…Therefore, the regulation and stabilization of Topo II␣ by p38␥ have important clinical implications. Although it has long been recognized that Topo II-targeting drugs are more effective in ER-negative breast cancer patients, the mechanisms have been mostly unknown (41,42). While the cytotoxicity of Topo II drugs is directly correlated with Topo II␣ levels (40), clinical studies have failed to show any connection between Topo II␣ and ER protein expression in primary breast cancer (43), indicating that other factor(s) must regulate Topo II␣ levels and the activity of Topo II drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the regulation and stabilization of Topo II␣ by p38␥ have important clinical implications. Although it has long been recognized that Topo II-targeting drugs are more effective in ER-negative breast cancer patients, the mechanisms have been mostly unknown (41,42). While the cytotoxicity of Topo II drugs is directly correlated with Topo II␣ levels (40), clinical studies have failed to show any connection between Topo II␣ and ER protein expression in primary breast cancer (43), indicating that other factor(s) must regulate Topo II␣ levels and the activity of Topo II drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the predictive role of HER2 status and TOP2A abnormalities has been challenged by controversial findings across different series [10] and by the results of a meta-analysis [29]. However, a pooled analysis of adjuvant trials indicates that both TOP2A abnormalities and/or duplication of CEP17 independently predict for anthracycline responsiveness [30], and recent attention has turned again on reappraising the role of TOP2A.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, despite conflicting results, observational studies indicated that HER2 amplification or HER2 overexpression, along with topoisomerase 2 alpha (TOP2A) genomic abnormalities, is a potential predictive biomarker of benefit from adjuvant epirubicin-based chemotherapy [10]. The topoisomerase 2 alpha protein is the gene product of TOP2A, and it is a key molecular target of anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the tremendous amount of evidence, the impact of ER, PR, HER2, and Topo IIα expression on the efficacy of neoadjuvant chemotherapy remains controversial (Järvinen et al, 1998;Di Leo et al, 2001;Harris et al, 2001;Coon et al, 2002;Lips et al, 2012). For example, some findings suggest that HER2 overexpression or gene amplification together with Topo IIα positive or negative status could collectively predict the response to anthracycline-based chemotherapy; however, this finding has been questioned by other studies (Di Leo et al, 2002;Järvinen et al, 2003;Arpino et al, 2005;Fritz et al, 2005;Harris et al, 2009;Munro et al, 2010). Moreover, an increasing number of factors, such as Ki67, oncoprotein K-RAS, and tumor suppressor p53, have been proposed to affect neoadjuvant chemotherapy in breast cancer, but the overall consensus remains inconclusive (Bonnefoi et al, 2011;Dowsett et al, 2011;Generali et al, 2011;Oshima et al, 2011;Petrarca et al, 2011).…”
Section: Introductionmentioning
confidence: 63%